Role of lipid deterioration on the quality of aquatic products during low‐temperature storage: a lipidomics‐based study using large yellow croaker (Larimichthys crocea). (26th November 2021) - Zhao, Tengfei; Sheng, Bulei; Ying, Xiaoguo; Sanmartin, Chiara; Benjakul, Soottawat; Ma, Lukai; Xiao, Gengsheng; Liu, Guoqin
Abstract: This work investigated the effects of different storage periods (0 day, 90 days, 120 days) on the quality of large yellow croaker oil. The lipomics of large yellow croaker oil was quantitatively detected by GC‐MS, the content of triglyceride in large yellow croaker oil reached 52.56% at 0 day. With the extension of storage time, the content of large yellow croaker oil components decreased gradually. Differential lipid histogram clearly indicates that the extension of the storage period will affect the change of fish oil, due to the rise in the temperature of large yellow croaker oil; the color of the hot map is bright from the dark. Additionally, the fatty acid composition and volatile components were measured. At 120 days, the decomposition rate of lipid molecular in large yellow croaker oil is increased by oxidation of unsaturated fatty acids, and its oxidised metabolite produced small substance such as aldehydes, ketones, alcohols, and acids. During storage, the waxy, fat, and floral flavour in the oil aroma of large yellow croaker oil decreased gradually, while the yeast flavour and oil flavour increased gradually. These results provide insights for the study of lipid transformation and quality of large yellow croaker oil during different storage. Abstract : The lipid deterioration played a key role on the physicochemical property of large yellow croaker during the low‐temperature storage.